Comparative study on settlement calculation of clay core rockfill dam by different constitutive models. Issue 1 (June 2021) - Zhang, Zhe-Yu; Ding, Chun-Mei
Abstract: The analysis and calculation of the settlement of the clay core rockfill dam is decided by the constitutive relation of the dam material. In this paper, the settlement of the clay core rockfill dam of Luding Hydropower Station under different working conditions is analyzed and calculated by using Duncan E-v and double yield surface elastic-plastic model. E-v model is quite sensitive to Poisson's ratio, and the small changes of parameters G, D and F may lead to great differences in the deformation calculation results of the model, while the elastic-plastic model with double yield surface is not very sensitive, and its settlement calculation results under different working conditions are relatively stable.